No cinema com a psicanálise: Seven e a perversão - Azevedo, Natanael Duarte de (2012)
This present paper intends to works with studies about perversion, including the conception of deviant sexuality, from Middle age, to the structuralist studies proposed by Jacques Lacan, verifying in the movie Seven, by David Fincher, the possibility of interpreting that John Doe s acts are characteristics of perversion. Our object is to demonstrate how the serial killer s actions in the movie Seven can reveal movements of the unconscious that follow a motivation/manipulation of desire. To accomplish our goal, we will resort to three lines of theoretical discussion: 1) the perversion under the vision of fetishization (objectification of the sexual desire), the brain degeneration, the substitution of the desire and psychological structure (Cf. ROUDINESCO, 2008; BINET 1904 [1879]; KRAFFT-EBING (apud ROUDINESCO, 2008); FREUD, 1989 [1905]; LACAN, 1988 [1956] and 1999 [1958]);2) the seven capital sins as a way of maintenance and reintegration of the power of the church (Cf. DELUMEAU, 2003; LE GOFF, 2011; AQUINO, 2000); 3) the filmic adaptation through the prism of transtextuality (Cf. STAM, 2006; ANDREW, 1984; HUTCHEON, 2011). We analyze the film Seven seeking to infer from the crimes committed by the murderer John Doe, the movements of the unconscious that reveal the diviation of the desire to objectification of the victims. We realize that the diviation of the sexual objects can be seen both from the point of view of the religious inversion such as psychoanalysis. For our analysis, we will show the verbal and visual texts of the murders presented by the film, then, we propose the analysis of the sequence of crimes based on two types of perversion: voyeuristic (pleasure to look at the other) and sadism (pleasure to overpower the other). We observed in our research the intrinsic relationship between voyeur and sadistic acts and religious motivation witch can determine the crimes by the purification of the capital sins. Thereby, with the possibility of reading the film Seven as an adaptation based on source texts that deal with themes such as sin and transgression of the law, we saw that the construction of the film reveals us a (re) reading of the texts about capital sins and clinical work with perversion patients.